ФОРМИРОВАНИЕ ТЕРРИТОРИАЛЬНЫХ МИНЕРАЛЬНО - СЫРЬЕВЫХ КОМПЛЕКСОВ В РЕСПУБЛИКЕ КАРАКАЛПАКСТАН - Ешимбетов, У.Х.; Искендеров, А.Б.; Турдыбекова, З.М.; Атамуратов, И.А. (SCIENCE and SOCIETY, 2022)
The article is devoted to territorial mineral resource complexes formed on the basis of local mineral resources. In the future, they should be formed in the Republic of Karakalpakstan. The specific capabilities of each territorial mineral resource complex were analyzed. The directions of their development have been studied. The issues of organizing clusters based on mineral resources were also considered.